Identification of the As-bearing phases in fresh volcanic Andean ashes - Bia, Gonzalo Luis (2014)
Fil: Bia, Gonzalo Luis.Consejo Nacional de Investigaciones Científicas y Técnicas. Centro de Investigaciones en Ciencias de la Tierra; Argentina.